REPRODUCTIVE PERFORMANCE OF SHEEP IN MIGRATORY AND NON-MIGRATORY FLOCKS IN SOUTHERN TAMIL NADU - A. Singaravadivelan; N. Kumaravelu; T. Sivakumar; S.M.K. Karthickeyan; D.Vinothkumar; D. Divyalakshmi (Indian Journal of Veterinary and Animal Sciences Research, 2024)
A study was conducted to analyse the migratory sheep production system in southern agro-climatic zone of Tamil Nadu. Reproductive performance of the rams and ewes was recorded through the questionnaire both in migratory and non-migratory flocks. Mean lambing percentage, twinning percentage, livability at birth percentage, age at first mating (months) in ewes, age at first mating (months) in rams, age at first lambing (months) and weaning percentage in migratory and non-migratory flocks were 93.56 and 91.50; 1.87 and 1.52; 98.32 and 98.73; 12.34 and 13.22; 19.64 and 21.44; 18.54 and 19.68; 85.98 and 87.15, respectively. The weaning period for ram and ewe lambs were 2.94+0.96 and 5.03+0.13 in migratory flocks and 4.82+0.13 and 6.06+0.17 in non-migratory flocks, respectively. Reproductive performance of sheep in migratory flocks was significantly better than nonmigratory flocks. The months of October,  November and December were main lambing season and the months of April and May were second lambing season.